2000
DOI: 10.1074/jbc.275.11.7447
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of Human DNA Polymerase η

Abstract: Xeroderma pigmentosum (XP) patients are highly sensitive to sunlight, and they suffer from a high incidence of skin cancers. The variant form of XP results from mutations in the hRAD30A gene, which encodes the DNA polymerase in humans, hPol. Of the eukaryotic DNA polymerases, only human Pol and its yeast counterpart have the ability to replicate DNA containing a cis-syn thymine-thymine (T-T) dimer. Here we measure the fidelity of hPol on all four nondamaged template bases and at each thymine residue of a cis-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
350
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(378 citation statements)
references
References 23 publications
23
350
1
3
Order By: Relevance
“…Pol η also replicated the unmodified template, forming all four base substitutions (Figs 3 and 4). This highly error-prone nucleotide incorporation supports previous findings that the enzyme replicates normal DNA with low fidelity (45)(46)(47). Some of this may be explained by a loose requirement of the polymerase for correct Watson-Crick base-pairing geometry.…”
Section: Discussionsupporting
confidence: 89%
“…Pol η also replicated the unmodified template, forming all four base substitutions (Figs 3 and 4). This highly error-prone nucleotide incorporation supports previous findings that the enzyme replicates normal DNA with low fidelity (45)(46)(47). Some of this may be explained by a loose requirement of the polymerase for correct Watson-Crick base-pairing geometry.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, two-thirds and one-third of UV-induced CPDs in cells are thymine-thymine and thymine-cytosine photoproducts, respectively. On the other hand, it was clearly shown that thymine-thymine CPDs are largely bypassed in an accurate manner by human Pol (28,41,42). Hence, inactivation of Pol renders cells hypermutable and mice susceptible to cancer by UV irradiation.…”
Section: Role For Pol In Prevention Of Uv-induced Mesenchymal Tumorsmentioning
confidence: 99%
“…Dois modelos explicam como isso poderia acontecer: A inserção sempre de adenina oposta a um dímero por polimerases síntese translesão ou a replicação de uracila, resultado da desaminação da citosina em um dímero de pirimidina. comparado às polimerases clássicas da família B (McCulloch e Kunkel, 2008), entretanto, dependendo da polimerase TLS recrutada, a lesão pode ser replicada praticamente sem erro como Pol η tendo CPD de timinas (T^T) como molde (Johnson et al, 2000). A outra lesão gerada por luz UV, o díme-ro 6-4PP, possui uma distorção muito maior e não pode ser replicada por Pol η e estudos indicam que Pol ζ e REV1 são necessárias para transpor essa lesão, porém com maior taxa de mutagênese (Nakajima et al, 2004).…”
Section: Luz Uv E Consequências Dos Fotoprodutosunclassified